Chronic Pancreatitis in Elderly: Does Idiopathic Senile Pancreatitis Exist as an Entity? - Tumelero, Tiziana; Amodio, Antonio; Frulloni, Luca; Benini, Luigi; Gabrielli, Armando; Vantini, Italo (JOP. Journal of the Pancreas, 2013)
Context Chronic pancreatitis (CP) is not common in elderly people. Idiopathic senile pancreatitis (SP) was described 30 years ago, occurring over 50s, but very little information was reported since that first reported so far. Painless course, steatorrhea or diabetes, and pancreatic calcification were the clinical features. Objective This study was aimed at identifying presence and characteristics of SP in patients with CP aged >65 years. Fifty patients out of a series of 620 CP (8.1%) were identified. In 28 the onset of CP occurred >65 years (Group A), in 22 it occurred before the age of 65 years, but they were referred to our unit after 65 years (Group B). Methods Demographic data, risk factors, clinical features, morphological changes, exocrine function, diabetes were collected. Parametric and non-parametric statistical analysis was carried-out. Results No difference in gender, alcohol consumption (30% of abstainers), smoking (36% of non-smokers), genetic factors was observed between the two groups, though heavy drinkers were 25% in Group A and 40.5% in Group B (P=0.360). Heavy drinkers were also smokers. 25.3% (7 cases) of Group A and 40.5% (9 cases) of Group B were classified as alcoholic CP. Obstructive CP was present in 28.6% of A (8 cases) and 18.8% (4 cases) of Group B (P=0.304). In 22 patients (44.0%) (13 A: 46.4%; 9 B: 40.1%) CP was idiopathic (P=0.46). Painful relapses were observed in 60.7% of Group A and 86.3% of B (P=0.04). No difference in jaundice, body weight loss, diabetes, age of onset and duration of diabetes, and exocrine insufficiency was found. Calcifications were found in 71.4% and 77.3% of A and B respectively. Wirsung duct dilation (>3 mm) was observed in 92.8% and 81.8% of the two groups, and the mean pancreatic duct size was 7.36±0.44 and 7.55±1.01 (P=0.856). Fourteen patients were painless pancreatitis, preceded by painful relapses in a single case. Out of the 13 primary painless CP, 10 (76.9%) belong to Group A, 3 (23.1%) to Group B, being painless CP represented in 35.7% of A and 13.6% of B patients (P=0.044). Alcohol intake was 52.7±16.1 and 24.0±8.2 g/day in non-painless and painless CP of Group A (P=0.01). Five of the 10 CP (A) and 2/3 cases (B) were idiopathic CP (idiopathic senile CP) (17.9% of group A). Conclusions CP with onset or diagnosis over 65 years is not clinically and morphologically different from CP in patient referred over 65 years, but with a preceding onset, except for a higher frequency of primary painless CP. Idiopathic senile CP represents a very small group (10% of patients with CP observed over 65 years), without clinical, morphological and functional distinction from the other CP patients. It does not seems to be a clinical-pathological entity.